Ranking the methods to improve asset-liability management in commercial banks of Iran using the hybrid MCDM approach (case study: Tehran branches of Sepah Bank) - Seyed Fakhreddin Fakhrhosseini; Meysam Kaviani (تصمیم گیری و تحقیق در عملیات)
Purpose: The main objective of this study is to rank methods of improving debt-asset management at branches of Bank Sepah in Tehran.Methodology: Questionnaires were the tool to collect data, and statistical sample is 146 managers and experts of Bank Sepah in Tehran that have been selected by the simple random sampling method. In this study, by using Multiple Criteria Decision-Making (MCDM) techniques of fuzzy TOPSIS, we have ranked the goals of debt asset management in Bank Sepah.Findings: Based on the results, among the main criteria for Asset and Liability Management (ALM) goals, “the risk management of interest rate” with a weight of 3. 83 is at the first priority, then the “maintenance of adequate capital” with a weight of 3. 67 is in the second place and then “liquidity risk management” with a weight of 3. 41 is in the third priority. Also, according to Friedman test results؛ there are differences between the achievements for each of the major debt-asset management in Bank Sepah in Tehran.Originality/Value: This study is a mixed method (Delphi (qualitative) and survey (quantitative)) in terms of performance and in terms of data collection. By using MCDM techniques, we have ranked the major objectives of asset-debt management in Bank Sepah. In addition, the results could be used in the planning process of banks and financial institutions.